Gendered Wage Penalties for the Overeducated: The Experiences of Young Men and Women in Ten European Countries - Jagannathan, Radha; Camasso, Michael J. (Comparative Economic Research. Central and Eastern Europe, 2025)
In this study, we examine the impact of overeducation on wages and wage penalties among 19,000 young men and women aged 18–35 in ten European countries. Using data from the Cultural Pathways to Economic Self-sufficiency and Entrepreneurship (CUPESSE) project and controlling for some endogeneity from omitted ability variables and employment selection, we find that women’s wages and wage penalties align with job search theory, while men’s observed wage offers are consistent with job competition theory. However, once selection is accounted for, wage penalties incurred by young men do not follow the predictions from this theory. Despite lower baseline wages, women in many countries face larger overeducation penalties than men, a pattern shaped by institutional regime type and gender norms. We offer possible explanations for this disparity and conclude with policy recommendations to address overeducation penalties.